2019
DOI: 10.1021/acsomega.9b00856
|View full text |Cite
|
Sign up to set email alerts
|

CFD Simulation and Optimization of Mixing Behaviors in a Spouted Bed with a Longitudinal Vortex

Abstract: The radial mixing characteristics of gas and solid phases in a cylindrical spouted bed with a pair of longitudinal vortex generators (LVGs) are numerically studied by a two-fluid model. The influence of the distance between the centers of two spheres ( L ) and the shape of LVGs on hydrodynamics in a spouted bed are discussed. The results show that the value of the coefficient of variation (CV) of the particle concentration can be significantly reduced by the longitudinal vortex produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…When the jet diameter D = 4 mm, the number of jets is 24, and the nondimensional cross-sectional area of the air inlet is 0.67, the fluidization effect between fluids in the bed is optimal. In the case of spouted beds with LVGs, the law of fluid flow is explored by changing the number of rows, spacing, and diameter of the spherical generators. The simulation showed that when the number of rows of the spherical generators was 3, the spacing was 10 mm, and the diameter was 28 mm, the turbulence effect of the particles was the strongest.…”
Section: Introductionmentioning
confidence: 99%
“…When the jet diameter D = 4 mm, the number of jets is 24, and the nondimensional cross-sectional area of the air inlet is 0.67, the fluidization effect between fluids in the bed is optimal. In the case of spouted beds with LVGs, the law of fluid flow is explored by changing the number of rows, spacing, and diameter of the spherical generators. The simulation showed that when the number of rows of the spherical generators was 3, the spacing was 10 mm, and the diameter was 28 mm, the turbulence effect of the particles was the strongest.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the flow behavior of ultrafine powders in the spouted bed with coarse particles was numerically studied by Sun et al Zhang et al experimentally studied the gas–solid two-phase flow of silicon particles with a wide scale distribution in a draft tube spouted bed. Wu et al studied flow behaviors of gas and particles in three kinds of spouted beds recently: without disturbance units, with a pair of balls and with a pair of longitudinal vortex generators (LVGs). The effect of LVGs’ row number on the hydrodynamic behaviors in the spouted bed is also numerically analyzed.…”
Section: Introductionmentioning
confidence: 99%